A COMPARISON OF OBSERVE AND RULE BASED OPTIMIZATION ALGORITHM FOR PHOTOVOLTAIC MAXIMUM POWER POINT TRACKING - Wan Muhammad Faizal (Sekolah Tinggi Teknologi Pekanbaru, 2013)
The perturb and observe (P&O )in one of a optimization based control that have best operation condi- tions are investigated in order to identify the edge efficiency performances of this most popular maximum power point tracking (MPPT ) technique for photovoltaic (PV ) applications. It is shown that P&O may guarantee top-level efficiency. At the other a ruled control such as ANN propose a fast point assignment and a small error the point assignment. It is shown that ruled control may guarantee faster point assignment and a high-level efficiency. This paper compare both method based on the speed to get the maximum point and the efficiency of each algorithm.